TERAPI PASIR HITAM DI DESA GIRI EMAS KECAMATAN SAWAN KABUPATEN BULELENG BALI - Purba, Sery Nurmaya; Anom Kumbara, Anak Agung Ngurah; Wiasti, Ni Made (FISIP Universitas Malikussaleh, 2024)
The rapid development of autem modu modem is not always able to provide total and comprehensive healing to patients Complementing treatment that is popular with the people of Gin Emas Village, Sawan District, Buleleng Regency The chapter in dealing with black fungus therapy chooses therapeutic treatment as an alternative treatment. This can be seen in the beliefs and habits of the community in choosing therapy black pasu when suffering from broken bones. This study aims to describe the process of sexta mechanism of fracture treatment by black sand therapy and to explain the factors behind black sand therapy persisting as health care in the village of Giri Emas. This study uses symbolic interaction theory, health belief model theory and health behavior theory and pressure. The concepts used as guidelines in this research are black pasur therapy, survival, and the medical system. and literature study. Researchers are the main instrument of pre-research which is assisted by using interview guidelines with voice recorders, cameras and tools. The results of the research show that the methods and benefits of treating broken bones are black sand therapy, using massage techniques, massaging, and pulling the broken bones to return them to their original position. Hom aa sand therapy uses sand to clamp broken bones. On the other hand, black paste therapy still survive in the midst of modern medical developments that are increasingly popular. This is caused by several factors, namely the closeness of the patient to using tecami pasiz butam, the patient's cultural background factor that is the same as black sand therapy, the patient's trust factor in pari kiam therapy, the suggestion factor, and factor .